2013
DOI: 10.1186/1465-9921-14-29
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of circulating dendritic cell subsets in patients with atopic diseases and sarcoidosis

Abstract: BackgroundDendritic cells (DCs) are professional antigen-presenting cells that play a crucial role in the initiation and modulation of immune responses. Human circulating blood DCs are divided into two major subsets: myeloid DCs (mDCs); and plasmacytoid DCs (pDCs). Furthermore, mDCs are subdivided into two subsets: Th1-promoting mDCs (mDC1s); and Th2-promoting mDCs (mDC2s). Although CD1a, CD1c, and CD141 are generally used for classifying mDC subsets, their adequacy as a specific marker remains unclear. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
1
26
1
1
Order By: Relevance
“…Indeed, the addition of OX40L neutralizing antibodies to DC-T cell co-cultures substantially reduced the ability of CD141 + DCs to induce IL-13-secreting CD4 + T cells. Interestingly, CD141 + circulating DCs were found at significantly higher frequencies in subjects with house-dust mite allergy and asthma, compared with control subjects (44, 45). Moreover, CD141 expression in blood leukocytes was higher in children with acute asthma than at convalescence 6 weeks later (44).…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, the addition of OX40L neutralizing antibodies to DC-T cell co-cultures substantially reduced the ability of CD141 + DCs to induce IL-13-secreting CD4 + T cells. Interestingly, CD141 + circulating DCs were found at significantly higher frequencies in subjects with house-dust mite allergy and asthma, compared with control subjects (44, 45). Moreover, CD141 expression in blood leukocytes was higher in children with acute asthma than at convalescence 6 weeks later (44).…”
Section: Discussionmentioning
confidence: 93%
“…Dendritic cells (DC) are the main antigen presenting cells (APC) and exert a relevant role of linkage between the innate and adaptive immune responses . Recent studies suggest that DC also participate in the induction of central and peripheral immunological tolerance, regulate T cell immune responses, and function as sentinels in innate immunity against microbes …”
Section: Introductionmentioning
confidence: 99%
“…Human blood DC comprise around 1–2% of peripheral blood mononuclear cells (PBMC) . They are classically defined as APC that lack other markers of leukocyte lineages (CD3, 14, 16, 19, 20, and 56) and express high levels of MHC class II (HLA‐DR) molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that cowshed dust extract reduced the allergy-inducing capacity of bone marrow DCs of mice [18]. Allergies and asthma have been shown to be associated with the numbers of DCs in adults [19][20][21][22] and in children [23][24][25], but the effect of farm exposure on circulating DCs in epidemiological settings is mainly unexplored.…”
Section: Introductionmentioning
confidence: 99%